Імітаційне моделювання за допомогою Matlab Simulink системи мікроклімату в пташниках у літній період року - Троханяк, В. І.; Мірошник, В. О. (Energy and Automation, 2017)
UDC 536.2SIMULATION USING MATLAB Symulink microclimate systemin poultry houses in the summer seasonV. Trokhanyak, V. Miroshnyk Livestock for information capacity house is typical of secondary facilities management. Among the parameters for controlling it is the most important room temperature and harmful substances and moisture in the air. Number of harmful substances in the air is determined by the volume of air that enters the room and the number of animals in it. The temperature in the room is determined by heat loss to the environment and the costs for heating air to room temperature. Note that the livelihoods of biological object Tou animals leads to release heat, which should be considered when constructing a model of heat indoors farms and to release moisture and which should be considered when calculating the air flow in ventilation zahalnoobminnu aimed at removing moisture and carbon dioxide from space.The purpose of research - to develop a simulation model of thermal mass transfer, ventilation poultry premises in the summer, with the help of heat exchangers.Materials and methods of research. When creating a mathematical model of ventilation on the farm is the material balance of pollutants in indoor farms. An important factor is that the air flow, coming into the room Farm for ventilation. This option is used not only by channel temperature control, but also on the channel regulation purity of air. And here he is parameter control. Air consumption is calculated depending on a number of harmful factors that enter the air, water, carbon dioxide, methane, removing excess heat and so on., But to regulate choose the one factor that makes the most important air. According to traditional methods of calculation, in the summer, the largest air exchange is necessary to remove excess heat and been taken as a basis.The calculation of ventilation and heating in the summer, with the known methods.To create a model system MATLAB Simulink given equation dynamics of heat transfer to the Cauchy type.Results. The mathematical simulation model to maintain temperature in the poultry houses in the summer, with the help of MATLAB Simulink.Research on the model showed that the constant heating time will be 118.4 s. Performance ventilation is between 36 thousand. 170 thousand. m3/h. Really system simulation model in the summer, the temperature is stabilized Na humidity to 1000 s. The relative humidity is 60 %.ConclusionsA simulation mathematical modeling of climate in poultry houses in the winter, with the help of MATLAB Simulink. Found that the required air ventilation in the summer the temperature is stabilized Na humidity to 1000 seconds. The relative humidity is 70 %.